Pengaruh Kinerja Caddie terhadap Kepuasan Golfer dalam Pengalaman Bermain di Rainbow Hills Golf Club Bogor - Tatik Sriwulandari; Fajar Anugrah Subhi; Yoanna Yoanna (Jurnal Manajemen Bisnis Digital Terkini, 2024)
Caddie performance in golf is an important aspect that can influence a golfer's overall satisfaction. This analysis was conducted to answer the question of how Caddie performance impacts golfers' satisfaction in their golf experience. An inductive quantitative approach was carried out using the SPSS analysis tool through a questionnaire distributed to 171 respondents. The research results show that Caddie Performance has a positive and significant effect on Golfer Satisfaction. This was opened with a regression test which produced a t-count > t-table value of 4,493 > 1,654, so that H0 was rejected and H1 was accepted. The significance value also shows a value smaller than the research alpha (α) or 0.000 < 0.05, so it can be concluded that Caddie Performance has a positive and significant effect on Golfer Satisfaction (Y) at Rainbow Hills Golf Club Bogor in terms of the playing experience they gain. The coefficient of determination or R Square value obtained is 0.800 which is interpreted as the influence of the independent variable namely Caddy Performance (X) which is 0.800 or 80% of the dependent variable Golfer Satisfaction (Y) at Rainbow Hills Sentul Bogor, while the remainder is 0.200 or 20% influenced by other variables not included in this research. This can be a consideration for the management of Rainbow Hills Golf Club Bogor to always pay attention to Caddie performance in order to increase the satisfaction of golf players who are members of the club as well as improve the image of the golf club.